ϱ- TOPOLOGICAL OPERATORS IN TOPOLOGICAL SPACES - H., Shanmugapriya; K., Sivakamasundari (Science Journal of University of Zakho, 2023)
Operation Approach on a new class of topological spaces with -open subsets was called a -open set. In this article, we examined some basic properties of open sets such as closure, , limit points, derived sets, neighbourhood, interior, exterior, boundary, frontier and saturated set of already existing -open sets in topological spaces.